Evaluation antifongique de l’extrait méthanoïque de Salvia officinalis vis-à-vis de Colletotrichum sp. DEVANT LE - KHDIM, Bachir; MERROUCHE, Aimen (My University, 2022)
The present study aims to propose alternative solutions based on the use of natural products "biopesticides", in order to fight against tomato anthracnose, considered as double for this culture in Algeria. The sauge Salvia officinalis is a medical and aromatic plant of the Lamiaceae family, which contains phenols with an effect on fungi. On this, we carried out an “in vitro” test of hydromethanolic extracts on Colletotrichum sp. The results of the "in vitro" test of the effect of S. Officinalis leaves on myceliene growth and sporulation show a correlation between the doses of the two extracts (hydromethanolique extract by maceration and soxhlet) and the inhibition rates, indeed, the higher the dose, the lower the myceliene growth.
Keywords: Colletotrichum sp; Salvia officinalis; myceliene growth; sporulation; hydromethanolique; maceration; soxhlet